2010
DOI: 10.1007/s00421-010-1754-6
|View full text |Cite
|
Sign up to set email alerts
|

Short term effects of various water immersions on recovery from exhaustive intermittent exercise

Abstract: In order to investigate the effectiveness of different techniques of water immersion recovery on maximal strength, power and the post-exercise inflammatory response in elite athletes, 41 highly trained (Football, Rugby, Volleyball) male subjects (age = 21.5 ± 4.6 years, mass = 73.1 ± 9.7 kg and height = 176.7 ± 9.7 cm) performed 20 min of exhaustive, intermittent exercise followed by a 15 min recovery intervention. The recovery intervention consisted of different water immersion techniques, including: temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
157
1
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(177 citation statements)
references
References 34 publications
11
157
1
8
Order By: Relevance
“…Squat and countermovement jump height was assessed using a vaned jump and reach apparatus, which provides the maximum height reached to the nearest centimetre (Yardstick, Swift Systems, Lismore, Australia), with the best of three attempts being recorded in accordance with previous research (Ali et al, 2011;Pournot et al, 2011).…”
Section: Jump Performancementioning
confidence: 99%
“…Squat and countermovement jump height was assessed using a vaned jump and reach apparatus, which provides the maximum height reached to the nearest centimetre (Yardstick, Swift Systems, Lismore, Australia), with the best of three attempts being recorded in accordance with previous research (Ali et al, 2011;Pournot et al, 2011).…”
Section: Jump Performancementioning
confidence: 99%
“…Além disso, outros fatores como a depleção de substratos (principalmente glicogênio muscular), hipertermia e acúmulo de vários metabólitos, entre eles: magnésio (Mg2+), adenosina difosfato (ADP), fosfato inorgânico (Pi), amônia (NH3) e espécies reativas de oxigênio (ROS) 11 . Estratégias de recuperação com o objetivo da manutenção do desempenho têm sido amplamente estudadas [12][13][14][15] . Em especial a RA e RG (i.e.…”
Section: Discussionunclassified
“…Os resultados apontaram queda no desempenho dos testes neuromotores para ambos os grupos que envolviam a aplicação de gelo. Por outro lado, mais recentemente, foi demonstrado que a RG é considerada um importante método para recuperação dos níveis de força e potência após a realização dos exercícios anaeróbios intermitentes 15 , embora pareça não ser tão efetiva para a remoção do La -19 . Resultados similares também foram encontrados por Vaile et al 12 , que verificaram melhor manutenção no desempenho utilizando a RG quando comparado à RA, mesmo com vantagem para a RA na remoção do lactato.…”
Section: Discussionunclassified
“…The thermal stimulation of contrast water immersion was considered to contract and relax subcutaneous blood vessels as responses of the circulatory system, i.e., "a pumping effect"; but the authors concluded that it is necessary to investigate more closely the cardiovascular function in the recovery phase, such as HR, SV, CO, and blood pressure, in addition to muscle and skin blood flow. Similarly, in a study in which a maximal performance test was performed during the recovery process after exhaustive intermittent exercise (10 min, 2 sets) 27) , water immersion was effective for recovery of the performance. In this study, 15-minute cold water immersion (10°C) or contrast water immersion (10°C, 42°C) was performed, setting the water level at the iliac crest while in a sitting position.…”
Section: Exercise Recovery By Water Immersionmentioning
confidence: 94%